Effect of Domestic Chicken Eggshell Paste Against Dental Email - Any Setyawati; Febri Silviana (Denta Journal Kedokteran Gigi, 2019)
Background: Dental caries is caused by interactions between microorganisms, food, teeth, and time which can reduce the pH of the oral cavity to become acidic. The decrease in pH in the oral cavity can cause the demineralization process of teeth in the form of dissolved hydroxyapatite crystals which are the main constituents of tooth enamel. Hydroxyapatite which dissolves continuously can cause the formation of microporosity in tooth enamel. Domestic chicken eggshells contain high calcium carbonate. Calcium carbonate can be converted into hydroxyapatite through the precipitation method, so that hydroxyapatite produced from domestic chicken eggshells can be used as a substitute for hydroxyapatite enamel which is soluble due to the influence of acid. Objective: To determine the effect of domestic chicken eggshell paste on email. Research Methods: Types of experimental laboratory research. Five permanent premolar teeth were applied to acid etching for 60 seconds, so that enamel microporosity was formed and observation was carried out with a Scanning Electron Microscope (SEM). Furthermore, the application of chicken eggshell paste for 30 minutes for 14 days and observed by SEM. Results: a visible decrease in the enamel microporosity of tooth formed due to acid etching, in the form of email porosity closed after application of chicken eggshell paste for 14 days. Conclusion: domestic chicken eggshell paste can influence the surface of enamel.